PQRS (Preview, Questions, Read, and Summarize) Strategy for Teaching Reading Skill: An Action Research at Indonesian Senior High School Students - Praja, Faradiva Shalikha Noor; Nurmawati, Fitri; Maximilian, Aksendro; Febriyanti, Febriyanti (Universitas Lampung, 2024)
It is evidence that the literacy and reading proficiency for Indonesian students need to be enhanced. Therefore, the objective of this study is to enhance the reading proficiency and learning engagement of eleventh-grade students at SMA Persada Bandar Lampung in the academic year 2023/2024 through the implementation of the Preview, Question, Read, Summarize (PQRS) strategy. The research involved twenty-two students and followed the Classroom Action Research (CAR) approach, consisting of planning, acting, observing, and reflecting phases within each research cycle. Notably, the progress in students' learning engagement is evident in the mean scores, with the first cycle averaging 35.32 and the second cycle averaging 38.50, indicating an improvement of 3.18 points. Additionally, there was a noteworthy enhancement in students' reading proficiency, illustrated by the mean scores for their learning activities: 58.52 in the first cycle and 70.45 in the second cycle, reflecting an improvement of 11.93 points. These findings affirm that the PQRS Strategy effectively enhances both students' reading ability and their engagement in learning activities. Therefore, it is important to recommend PQRS teaching strategy to be used in English class.Keywords: CAR, Reading Comprehension, PQRS (Preview, Question, Read, and Summarize) Strategy